2007
DOI: 10.1038/sj.bjc.6603764
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E mutation in anaplastic thyroid carcinomas and their accompanying differentiated carcinomas

Abstract: Frequency of a BRAF V600E mutation in anaplastic thyroid carcinoma, which is thought to be derived mainly from papillary carcinoma by multi-step carcinogenesis, is much lower than that in papillary carcinomas. To clarify this phenomenon, we analysed BRAF V600E mutation in 20 cases of anaplastic carcinoma and 13 accompanying differentiated carcinomas. Among twenty cases of anaplastic carcinomas, nine and four accompanied papillary and follicular carcinomas, respectively. BRAF V600E mutation was found in four (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 19 publications
0
25
1
2
Order By: Relevance
“…Some studies also found a correlation of BRAF mutation with high-risk clinicopathological characteristics of PTC within specific subtypes, such as conventional PTC (66,68,71) and follicular variant PTC (74). Several studies showed that PTC components often existed in BRAF mutation-harboring ATC tumors and, in such cases, the PTC and ATC components usually both harbored BRAF mutation (76,(93)(94)(95). This suggests that BRAF mutation may play a role in promoting the progression of PTC to ATC.…”
Section: B Association Of Braf Mutation With the Most Aggressive CLImentioning
confidence: 99%
“…Some studies also found a correlation of BRAF mutation with high-risk clinicopathological characteristics of PTC within specific subtypes, such as conventional PTC (66,68,71) and follicular variant PTC (74). Several studies showed that PTC components often existed in BRAF mutation-harboring ATC tumors and, in such cases, the PTC and ATC components usually both harbored BRAF mutation (76,(93)(94)(95). This suggests that BRAF mutation may play a role in promoting the progression of PTC to ATC.…”
Section: B Association Of Braf Mutation With the Most Aggressive CLImentioning
confidence: 99%
“…BRAF mutations may be enriched in TCV PTC; one study demonstrated that all six TCV PTC cases harbored the BRAF mutation (20). In addition, anaplastic carcinomas (two of three cases, and three of nine cases) with adjacent TCV PTC also tested positive for the BRAF mutation (20,21). However, BRAF mutations are seen at all stages of PTC, including papillary microcarcinomas, indicating that additional mutations must take place for dedifferentiation to occur.…”
mentioning
confidence: 99%
“…RET/PTC and PAX8-PPARγ1 rearrangements are observed in a high prevalence of differentiated carcinomas but they are not detected in anaplastic carcinomas [13,14]. Furthermore, in five major studies carried out in Japan targeting patients with similar ethnic and environmental backgrounds, BRAF mutations were found in 39.7 % (378 out of 951) of papillary carcinomas, but only 18.1 % (6 out of 33) of anaplastic carcinomas, even though papillary carcinoma occupies about 90% of differentiated thyroid carcinoma in Japan [15][16][17][18][19].…”
mentioning
confidence: 99%